Implementasi Sistem Tracking Kereta Api dengan Protokol Publish Subscribe - Sapta Oryza Putra; Adhitya Bhawiyuga; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
It's a common sense that the railways as a means of transportation is needed by all kind of people. In previous studies, GPS train tracking is done with XML RPC technology. For each train that will going to be tracked, it's being installed with an Android based mobile device that comes with an application which will sends GPS's signals that contains position data at a certain time's interval to a server via a webservice mechanism by utilizing XML RPC technology. The author believes, the method of publish/subscribe can be used to replace the method in the previous studies without having a result that inferior to XML RPC client-server. This study uses MQTT protocol (MQ Telemetry Transport) and Mosquitto broker to implement publish/subscribe architecture. Finally, it can be concluded that the quality of the produced delay is in compliance with the author's hypothesis, that the delays required to deliver messages generated by the publish/subscribe protocol are smaller than XML RPC protocol's delays, as has been shown in the preliminary research, where the resulting delay of XML RPC protocol are always greater than MQTT. This is being proved using 2 testing scenarios for each protocol, these are one-to-many testing and many-to-one testing.